Semiotic Analysis of the Malay Palang Pintu Tradition in Medan Traditional Malay Weddings - Ihsan Al Fathir; Taufiq Nurrahmad; Elpiana Rossa; Hasan Sazali; Maulana Adinata Dalimunthe (Penerbit Jurnal Indonesia, 2022)
Research on Semiotic Analysis of the Malay Cross Door Tradition in Malay Traditional Weddings in Medan City aims to analyze, know and understand the meaning of the Malay Palang Pintu tradition which is commonly used in traditional Malay wedding processions in the city of Medan. The research was conducted using an Interpretative Qualitative research method and in more depth using the semiotic model method developed by Roland Barthes, which is a science and method used to analyze a sign that is carefully and based on facts in the field when researching the Malay Cross Pintu Tradition in Marriage. Medan City Malay Traditions. Data collection was carried out by direct observation of traditional Malay weddings using the Palang Pintu tradition, using books and previous research, and conducting interviews with traditional leaders or Telangkai from the Palang Pintu tradition. Based on the discussion and findings in the field, it is known that the Palang Pintu tradition itself has the aims and objectives of teaching and learning about obligations that must be carried out after marriage. In the Malay Palang Pintu tradition, it also means that the husband really holds the leadership of the household, starting from facing all kinds of obstacles, to putting patience to achieve good and healthy household goals.